2018
DOI: 10.1364/ao.57.001689
|View full text |Cite
|
Sign up to set email alerts
|

Coherent midinfrared supercontinuum generation using a rib waveguide pumped with 200  fs laser pulses at 28  μm

Abstract: A rib waveguide structure in AsSe chalcogenide glass has been designed and numerically analyzed for on-chip coherent supercontinuum generation in the midinfrared region. The waveguide structure possesses an all-normal dispersion profile with dispersion value of -13.22  ps/nm·km at the pump wavelength. Coherent midinfrared supercontinuum spectrum spanning 1.2 to 7.2 μm has been obtained using a 2.5 mm long rib waveguide when pumped with 200 fs laser pulses of a peak power of 2.5 kW and a repetition rate of 1 kH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The demonstrated tellurite glass ANDi PCFs also extend the current state-of-the-art in fibers designed for pulse-preserving, femtosecond supercontinuum generation, under pumping with lasers operating at standard wavelengths. Up to date, this line-up included fibers made of silica and germanium-doped silica fibers [28,29] and highly nonlinear silicate fibers [39], as well as ANDi chalcogenide glass fibers and waveguides, enabling at least an octave of normal dispersion supercontinuum under femtosecond pumping around 2070 nm [41] or at around 2700-2800 nm [42][43][44][45]. Fig.…”
Section: Discussion Of Experimental Results With Physical Fibersmentioning
confidence: 99%
“…The demonstrated tellurite glass ANDi PCFs also extend the current state-of-the-art in fibers designed for pulse-preserving, femtosecond supercontinuum generation, under pumping with lasers operating at standard wavelengths. Up to date, this line-up included fibers made of silica and germanium-doped silica fibers [28,29] and highly nonlinear silicate fibers [39], as well as ANDi chalcogenide glass fibers and waveguides, enabling at least an octave of normal dispersion supercontinuum under femtosecond pumping around 2070 nm [41] or at around 2700-2800 nm [42][43][44][45]. Fig.…”
Section: Discussion Of Experimental Results With Physical Fibersmentioning
confidence: 99%
“…shot to shot coherence over the entire SC output 20 . Planar waveguides alternative to the microstructured fibers, nowadays, are being considered for broadband SC sources design due to their short interaction length, scalable and low cost integrated optical chip fabrication [21][22][23][24][25][26][27] .…”
Section: Fig 1: Channel Waveguide Geometrymentioning
confidence: 99%
“…To date, a few of the following longest wavelength theoretical and experimental SC spectral evolution were demonstrated through optical planar waveguide and fiber based designs [24][25][26][27][28][29][30][31][32] . Yu et al 24 reported SC generation spanning up to the MIR covering the wavelength range 2 to 10 µm by an all-ChG rib waveguide using GeAsSe and GeAsS glasses for its upper and lower claddings, respectively, with 330-fs pulses pumped at 4.184 µm with an input peak power of 4.5 kW.…”
Section: Fig 1: Channel Waveguide Geometrymentioning
confidence: 99%
“…In 2017, Petersen et al demonstrated mid-infrared SC generation in a large-mode-area chalcogenide PCF taper [16]. In 2018, Saini et al investigated the coherent SC generation in chalcogenide W-type coaxial optical fiber, step-index tellurite fiber, and rib waveguide [17][18][19]. In the same year, Nguyen et al obtained mid-infrared SC with good coherence in cascaded tellurite and chalcogenide fibers [20].…”
Section: Introductionmentioning
confidence: 99%